Studies on saponins of leaf of Clerodendron thomsonae Balfour - Patrick-Iwuanyanwu, Sodipo (Acta Biologica Szegediensis, 2007)
In this study, the phytochemical screening of the leaf extracts of Clerodendron thomsonae Balfour were performed to ascertain one of its secondary metabolite constituents, saponin. The results revealed the presence of cardiac glycosides, flavonoids, alkaloids, glycosides and saponin glycosides. However, the plant extract was devoid of tannins, phlobatannins and anthracenes.The presence of saponins was detected by the formation of long-lasting foams and haemolysis of red blood cells. Phosphate-buffered saline (PBS) extract foamed with a height of 9.25 ± 0.4 mm and a foaming time of 20.93 ± 0.56 h while the methanol/phosphate buffered saline (M/PBS) extracts possessed a foam height of 3.75 ± 0.11 mm and disappeared fully after 27.37 ± 0.04 h. Generally, the foaming time was not proportional to the foam height. The melting point of both the aqueous and methanol crude extracts ranged between 283 to 315°C and 125 to 240°C, respectively. PBS and M/PBS extracts possessed haemolytic activities against human erythrocytes (ABO) but at varying degrees. The haemolytic activities for full and partial haemolysis of human red blood cells ranged between 1 to 2s and 23 to 2", respectively.